(untitled) (Research, Society and Development, 2021)
The presence of xenobiotic compounds in the environment is responsible for impacts on the ecosystem. An example is pesticides that pose risks to non-target species, such as microorganisms present in the soil and that are responsible for cycling nutrients, some can be used to measure the effects of these compounds, such as yeasts because when exposed to toxic substances begin to present changes in physiological and genetic mechanisms. Thus, this study aims to evaluate the toxicity effect of the 2,4-D pesticide on Pedra-2 (PE-2) and Fleischmann® (FLE) yeasts. 2,4-D dilutions of 2.0; 4.0 and 6.0 µg L-1 were added to a solution prepared with 20 ml of ultra-pure water and 2.0 g of sucrose where the yeasts were grown. The phenotypic profile of yeasts against the toxicity of the compound was evaluated quantitatively with cell viability. Using the methylene blue method and qualitatively with cell growth tests in Petri dishes containing 2% YPD medium and flocculation on slides with methylene blue. Yeasts showed loss of viability and the FLE strain showed greater sensitivity, the cellular growth of this yeast was also more affected and, consequently, presented higher flocculation rates. The data show that the longer exposure time and the doses and concentrations of 2,4-D interfered with the physiological response of the FLE yeast. Thus, we can suggest that this microorganism has the potential to be considered for environmental tests and analyses as a bioindicator.